RETRACTED: Development of distance learning of English for students of technical specialties based on the use of songs technology - Yekimov Sergey; Lebid Olha; Volkova Nataliia; Karpova Maryna; Sapozhnykov Stanislav; Klimchuk Yulia (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001